2016
DOI: 10.1016/j.jrras.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Study of the properties of soil in Kirkuk, IRAQ

Abstract: Gamma ray attenuation Neutron radiationMoisture-density gauge a b s t r a c tThe properties of soil in Kirkuk city (IRAQ) are studied using gamma and neutron radiation.Ten locations are selected for the process of making field measurements on soils at 40 e50 cm depth levels then the samples were collected to be studied in the laboratory also. In the field, we measured the density and moisture contents of soils. The laboratory measurement has been performed to obtain mass attenuation coefficients, using gamma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…4c). It was observed that in the worst cases (S-C-LOAM and S-LOAM) the emerging radiation intensity was less affected by the variation of the sample thickness (1.24 to 3.40 cm) [12]. Even being µ determined by the Beer-Lambert attenuation law close to that one determined by the XCOM, it is important to emphasize that the laboratory set up is prone to not produce accurate measurements of µ due to the lack of source and detector collimation as well as the type of detector and electronics used [13].…”
Section: Resultsmentioning
confidence: 99%
“…4c). It was observed that in the worst cases (S-C-LOAM and S-LOAM) the emerging radiation intensity was less affected by the variation of the sample thickness (1.24 to 3.40 cm) [12]. Even being µ determined by the Beer-Lambert attenuation law close to that one determined by the XCOM, it is important to emphasize that the laboratory set up is prone to not produce accurate measurements of µ due to the lack of source and detector collimation as well as the type of detector and electronics used [13].…”
Section: Resultsmentioning
confidence: 99%
“…Energy values from 10 to 1330 keV were explored (Figures 5a to 5f). The radiation interaction parameters for specific energies of the 241 Am (59.5 keV), 133 Ba (356 keV), 137 Cs (661.6 keV) and 60 Co (1330 keV) radioactive sources were also investigated as these sources are usually employed in soil radiation interaction studies (Kucuk et al, 2013;Taqi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We could see that these differences among soils influenced the radiation interaction parameters. Many authors have described the role of the chemical composition of materials in radiation attenuation (Kucuk et al, 2013;Taqi et al, 2016;Ferreira et al, 2018;Camargo et al, 2021;Pires et al, 2021). Recently, Pires et al (2019) demonstrated the relationship between the soil minerals and radiation interaction parameters, highlighting the particle density importance in the attenuation of the radiation by the matter (Al-Masri et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The linear attenuation coefficient (µL) is the decrease in photon beam intensity crossing an absorber material and can be determined by the Lambert-Beer rule [17],…”
Section: Theoretical Backgroundmentioning
confidence: 99%